Endodontic treatment of a hypertaurodont mandibular second molar with C-shaped canal: A case report - Shaikh Shahbaz; Sharique Alam; Surendra Kumar Mishra; Syed Mukhtar- (Wolters Kluwer Medknow Publications, 2021)
Taurodontism is a variation in tooth anatomy characterized by an enlarged pulp chamber with hypertaurodont being its most severe presentation. The complexity of endodontic treatment of hypertaurodont tooth may be compounded by coexistent C-shaped canal anatomy. A 26-year-old patient reported with spontaneous and lingering pain due to a deep carious lesion in the right mandibular second molar. Clinical and radiographic examinations were done. A diagnosis of symptomatic irreversible pulpitis with symptomatic apical periodontitis in a hypertaurodont with an associated C-shaped canal configuration was made. The cone-beam computed tomography image guide together with microscopic magnification was utilized to negotiate, clean, and shape the root canal system. The isthmus of the C-shaped canal was prepared with ultrasonic tips, while Endoactivator sonic irrigant activation was employed for effectively disinfecting of the uninstrumentable intercommunications, apical splits, and ramifications. The apical root canals were obturated by lateral condensation technique, while warm vertical compaction of gutta-percha was utilized to fill the remaining pulp chamber. A 1 year follow-up of the case reveals a functional tooth with no signs of periapical infection, indicating a successful treatment outcome.